Antiarrhythmic Drug Therapy in Arrhythmogenic Right Ventricular Cardiomyopathy - Sean P. Gaine; Hugh Calkins (Biomedicines, 2023)
Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a heritable progressive myocardial disorder that predisposes patients to ventricular arrhythmias and sudden cardiac death. Antiarrhythmic medications have an important role in reducing the frequency of ventricular arrhythmias and the morbidity associated with recurrent implantable cardioverter-defibrillator (ICD) shocks. Although several studies have examined the use of antiarrhythmic drugs in ARVC, these have been mostly retrospective in nature and inconsistent in their methodology, patient population and endpoints. Thus, current prescribing practices are largely based on expert opinion and extrapolation from other diseases. Herein, we discuss the major studies of the use of antiarrhythmics in ARVC, present the current approach employed at the Johns Hopkins Hospital and identify areas where further research is needed. Most notably, there is a great need for high-quality studies with consistent methodology and randomized controlled trial data into the use of antiarrhythmic drugs in ARVC. This would improve management of the condition and ensure antiarrhythmic prescribing is based on robust evidence.